The Effect of Poverty Rate, Gross Regional Domestic Product, Provincial Minimum Wage, and Unemployment Rate on the Human Development Index in 34 Provinces of Indonesia (2015–2024) - Putu Apriliani Prabawati; Akhmad Jufri (Golden Ratio of Auditing Research, 2026)
This study aims to analyze the influence of poverty level, Gross Regional Domestic Product (GDP), Provincial Minimum Wage (UMP), and unemployment rate on the Human Development Index (HDI) in 34 Indonesian provinces for the period 2015–2024. The study used a quantitative approach with secondary panel data from the Central Statistics Agency. The model used is the Fixed Effect Model (FEM) because it is able to control unobserved heterogeneity between provinces that is constant during the observation period. The estimated results showed that the poverty and unemployment levels had a negative and significant effect on HDI (p < 0.05), while GDP and UMP had a positive and significant effect (p < 0.05). Simultaneously, all independent variables had a significant effect on HDI with a probability value of the F test < 0.05 and a high coefficient of determination (R²), demonstrating the model's ability to explain variations in HDI between provinces. These findings confirm that improving regional economic performance and adequate wage policies contribute to improving the quality of human development, while poverty and unemployment are the main inhibiting factors. Therefore, development policies need to be focused on reducing economic inequality and increasing employment opportunities to encourage equitable distribution of human development in Indonesia.